Recent Trends in Regional Financial Integration and Trade Liberalization in Maghreb Countries: A Multivariate Threshold Autoregressive Analysis - Soumia Zenasni (FIW - Research Centre International Economics, 2015)
Increased globalization over the last two decades has led to strong growth in international business activity and international financial integration. This phenomenon covers a wide array of economic activities, including regional and international integration, investment and trade, international financial shocks and disturbances. This paper takes stock of current trends in regional financial integration and trade liberalization processes for the case of Maghreb countries. It aims also to examine the effects of these recent trends on economic growth in an era of growing globalization and frequent financial shocks. Using Multivariate Threshold Vector Autoregressive (MVTAR) estimation with data from 1990 to 2012, this study argues that the greater and deeper regional financial integration and trade will have positive repercussions for each Maghreb country. In addition, estimation results show that the regional financial integration process plays a positive role in enlarging the borders of countries as well as the market size of each country and, consequently, in stimulating economic growth. Finally, we can assert that the study argues that political and structural impediments continue to hamper regional integration.
Keywords: F36; E44; F65; G01; C3; 330; Regional financial integration; trade libaralization; globalization; Maghreb countries; multivariate threshold analysis